Analisis Kebutuhan Komponen Kondisi Fisik Atlet Cabang Olahraga Taekwondo Kategori Kyorugi pada Tim Kabupaten Gresik - Fahima Sovia; Fatkur Rohman; Achmad Widodo; Heri Wahyudi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Taekwondo is a martial arts sport that requires a combination of technique, tactics, and optimal physical condition to support athletes' performance. In the kyorugi category, components of physical conditions such as strength, speed, endurance, flexibility, and explosiveness are elements in determining the success of athletes in competitions. many athletes have not reached maximum performance due to the lack of targeted physical condition development. This study aims to analyze the needs of the physical condition components of taekwondo athletes in the kyorugi category in the Gresik Regency team. The research method used is an ex-post facto with a descriptive approach. The research subjects consisted of 8 athletes, athletes with measurements including sit-up, abdominal rollers, single leg squats, splits, standing broad jumps, and multistage fitness tests. The results showed that physical components such as speed, abdominal muscle strength, leg strength, muscle explosiveness, core strength, and endurance had a significant influence on athlete performance. flexibility was not found to be the main distinguishing factor between medal-winning and non-medal-winning athletes. The conclusion of this study is that the development of training programs that focus on increasing strength, endurance, and explosiveness is essential to support the achievements of taekwondo athletes in the kyorugi category.